IDENTIFIKASI BAHAYA DAN PENILAIAN RISIKO PROSES WTP (WATER TREATMENT PLANT) CV BORNEO ASRI REKATAMA BALIKPAPAN - Nuryanto, Nuryanto; Maslina, Maslina; Luqmantoro, Luqmantoro; Fariz, Luthfan (IDENTIFIKASI, 2022)
Hazard Identification and Risk Assessment (HIRA) is a method for determining and assigning hazards based on their probability, frequency and severity and evaluating their adverse consequences, including potential loss and injury. Work processes in industry must pay a lot of attention to environmental health and safety aspects in order to support industrial effectiveness. The industry must identify the hazard, assess its associated risks to tolerate a sustainable level, the risk assessment has been made using risk guidelines and standards. Control efforts must be systematic and comprehensive in a management that is integrated into the occupational safety and health program. In accordance with Government Regulation no. 50 of 2012 concerning the Occupational Health and Safety Management System article 11 which requires hazard identification, risk assessment and risk control to meet K3 requirements. CV Borneo Asri Rekatama Balikpapan is a company engaged in the distribution of clean water for PT HER housing in Balikpapan city where the hazards in the work environment of the clean water treatment area are in the form of physical hazards, biological hazards, chemical hazards, ergonomic hazards, and psychosocial hazards. The approach used is a qualitative research method. Data collection uses field research methods, interviews and observations, where the data is obtained by describing a list of questions that are quite detailed and complete about the object studied to the respondents. The results and discussion of the research, namely, in the process of operating the WTP is an activity that has a high risk and from the operational process activities of the WTP there are 8 risks that arise based on ISO 31000. After conducting an assessment, it is found that out of the 8 risks that appear 6 risks with a high risk level, 2 risk with a medium risk level of risk. After the risk has been handled with the OHSAS 18001 hierarchy of control, an assessment is carried out again on the remaining risks from control with the results of research on 8 risks down to 6 risks with a medium risk level and 2 risks with a low risk level.